Research Data Management Self-Education for Librarians: A Webliography. - Abigail Goben; Rebecca Raszewski (Issues in Science and Technology Librarianship, 2015)
The article offers information on websites about research data management, including California Digital Library DMPTools Webinars available at http://dmptool.org/community resources, New England Collaborative Data Management Curriculum available at http://library.umassmed.edu/necdmc and Lynda available at www.lynda.com/.